2011
DOI: 10.1590/s0066-782x2011005000093
|View full text |Cite
|
Sign up to set email alerts
|

Associação de diferentes medidas e índices antropométricos com a carga aterosclerótica coronariana

Abstract: Background: The association between anthropometric parameters and atherosclerotic burden is not well established and few studies have addressed this issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 21 publications
0
12
0
5
Order By: Relevance
“…Epidemiological evidence has suggested that abdominal obesity accelerates atherosclerotic progression, however, current evidence on the topic is limited and inconsistent 2, 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological evidence has suggested that abdominal obesity accelerates atherosclerotic progression, however, current evidence on the topic is limited and inconsistent 2, 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Neck circumference (NC) was recently associated with various cardiovascular risk factors such as insulin resistance and biochemical components of metabolic syndrome such as fasting glucose, fasting triglycerides, and blood pressure, independent of body mass index (BMI) and waist circumference [[1]-[4]]. However, few studies have assessed the relation between NC and early stage atherosclerosis in Chinese adults [[5]].…”
Section: Introductionmentioning
confidence: 99%
“…30 Para a RCEst, a maioria da população estudada está em risco (81,7%), semelhante ao observado por Silva et al (96,3%). 31 Chagas et al 32 citam a forte correlação da RCEst com a gordura intra-abdominal, e sua associação com maior risco para DCV. Diversos estudos têm demonstrado que a RCEst é um bom discriminador de obesidade abdominal relacionada a fatores de risco cardiovascular, bem como de risco coronariano elevado (RCE).…”
Section: Discussionunclassified